2016
DOI: 10.18517/ijaseit.6.2.613
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Breadfruit, Jicama, and Rice Starches as Stabilizer in Food Emulsion

Abstract: The aim of this research was to investigate the ability of three native starches from Indonesia to stabilize oil in water emulsion with and without the addition of lecithin as surfactant. Breadfruit, bengkuang (jicama), and rice starches were extracted from local sources in Banda Aceh-Indonesia. Two variables studied were type of starches and the amount of oil added into emulsion (15 and 25%). Proximate analysis showed that the starch content of breadfruit, jicama and rice were 77.57, 67.41, and 80.51% respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…(2007) , amylopectin fraction in OSA starch is responsible for interfacial functionality and during emulsification process these big molecules are quickly moved to the newly created oil-water interfaces. The proportion of amylopectin in BOSA starch was dominant (72.38%) compared to only 27.62% of amylose ( Anwar et al., 2016 ). The amylopectin structural attributes that contribute to the steric stabilization effectiveness are its large molecule size, its high backbone rigidity and its extensive chain branching ( Sweedman et al., 2013 ; Dokić et al., 2008 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…(2007) , amylopectin fraction in OSA starch is responsible for interfacial functionality and during emulsification process these big molecules are quickly moved to the newly created oil-water interfaces. The proportion of amylopectin in BOSA starch was dominant (72.38%) compared to only 27.62% of amylose ( Anwar et al., 2016 ). The amylopectin structural attributes that contribute to the steric stabilization effectiveness are its large molecule size, its high backbone rigidity and its extensive chain branching ( Sweedman et al., 2013 ; Dokić et al., 2008 ).…”
Section: Resultsmentioning
confidence: 95%
“…Among the starch sources, the breadfruit starch can be potentially used as a stabilizer in food emulsions. Anwar et al. (2016) explored the possibility of the usage of native starches, including jicama, rice, and breadfruit, as stabilizers in the O/W emulsions.…”
Section: Introductionmentioning
confidence: 99%
“….02 [180] 4.90±0.12 [186] -香蕉淀粉 轻微的黄色, 颜色有些发暗 [43] 76.30%-89.88% [178,179] 4.60 [127] -菠萝蜜淀粉 90%以上 [111,[181][182][183][184] 6.56-6.70 [187] 0.42-0.75 g/cm 3 [111,113,147,157,187] 面包果淀粉 白色, 除杂不彻底时为亮黄色 [177] 97.5%以上 [100,185] 4.73 [101] 0.28-0.33 g/cm 3[8, 101, 188] 芒果淀粉 淡白色偏黄色 79.63 [34] 6.26 [57] -蛋黄果淀粉 ---果肉淀粉: 0.47 g/cm 3 和种子淀粉: 0.62 g/cm 3 [60] A c c e p t e d [96,171,189] -0.54% [195] -60% [196] 2-60 g/g [93,148,197,198] 50%-70% [99] 香蕉淀粉 2 g/g 以下 [2, 42,43,109,126,161,163] 2-16 g/g [168,194] 5 g/g 以下 [163] 不超过 2 g/g [2,161,164] 0-26.5 mg/g [161,199]...…”
Section: 白度、Ph、堆积密度 表 7 特色热带作物淀粉的白度、Ph、堆积密度unclassified
“…The stability of native and modified breadfruit starch has also been investigated for their application in emulsion and baking based on rheological properties. Anwar et al (26) reported native breadfruit starch has good emulsion stability where high emulsification index (EI) than native jicama and rice starches. Storage stability test in room temperature also demonstrated that oil in water emulsion made from breadfruit starch had the lowest separation rate over storage period compared to jicama and rice emulsions.…”
Section: Stability Of Breadfruits Starch In Relation To Rheological M...mentioning
confidence: 99%